2017
DOI: 10.15580/gjpns.2017.1.122116217
|View full text |Cite
|
Sign up to set email alerts
|

Studying the effect of Gamma Ray on Morphological and Phenotypic Properties of Corn

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(5 reference statements)
1
1
0
Order By: Relevance
“…In the study conducted by (Abdelwhab et al, 2009), it was determined that there were changes in the protein, fat, carbohydrate, fiber, mineral, and vitamin values of irradiated dry beans. Similar determinations have been shown in different studies for products such as soybean, cowpea, and corn (Villavicencio et al, 2000;Mudibu et al, 2012;Sarker et al, 2014;Mirhabibi et al, 2016;Vahapoglu et al, 2022). The occurrence of such changes in food and the use of irradiation for mutation purposes in plant breeding studies are proof that the effect of gamma rays cannot be neglected (Well et al, 2022;Yasmin and Arulbalachandran, 2022).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In the study conducted by (Abdelwhab et al, 2009), it was determined that there were changes in the protein, fat, carbohydrate, fiber, mineral, and vitamin values of irradiated dry beans. Similar determinations have been shown in different studies for products such as soybean, cowpea, and corn (Villavicencio et al, 2000;Mudibu et al, 2012;Sarker et al, 2014;Mirhabibi et al, 2016;Vahapoglu et al, 2022). The occurrence of such changes in food and the use of irradiation for mutation purposes in plant breeding studies are proof that the effect of gamma rays cannot be neglected (Well et al, 2022;Yasmin and Arulbalachandran, 2022).…”
Section: Resultssupporting
confidence: 80%
“…But it has interacted with radiation and absorbed it. In addition, studies have shown that irradiation causes changes in protein, fat, carbohydrate, and vitamin values in food (Ayhan, 1992;Villavicencio et al, 2000;Karadag and Gunes, 2005;Abdelwhab et al, 2009;Mudibu et al, 2012;Sarker et al, 2014;Mirhabibi et al, 2016;Yılmaz and Ulger, 2016;Vahapoglu et al, 2022). In the study conducted by (Abdelwhab et al, 2009), it was determined that there were changes in the protein, fat, carbohydrate, fiber, mineral, and vitamin values of irradiated dry beans.…”
Section: Resultsmentioning
confidence: 99%